2016
DOI: 10.1371/journal.pone.0154631
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of the Endangered Aquilaria (Thymelaeaceae) and Its Application in Species Authentication of Agarwood Products Traded in the Market

Abstract: The identification of Aquilaria species from their resinous non-wood product, the agarwood, is challenging as conventional techniques alone are unable to ascertain the species origin. Aquilaria is a highly protected species due to the excessive exploitation of its precious agarwood. Here, we applied the DNA barcoding technique to generate barcode sequences for Aquilaria species and later applied the barcodes to identify the source species of agarwood found in the market. We developed a reference DNA barcode li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 40 publications
(44 reference statements)
6
56
1
1
Order By: Relevance
“…Our results have clearly demonstrated that DNA barcoding using only a single DNA locus was insufficient to provide resolution for Dalbergia species. These results are similar to previous finding for Aquilaria species (Lee et al 2016).…”
Section: Discriminant Power Of Barcodes From Dalbergia Woodsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results have clearly demonstrated that DNA barcoding using only a single DNA locus was insufficient to provide resolution for Dalbergia species. These results are similar to previous finding for Aquilaria species (Lee et al 2016).…”
Section: Discriminant Power Of Barcodes From Dalbergia Woodsupporting
confidence: 93%
“…In recent years, DNA methods to verify species identity and origin of internationally traded woods have attracted increasing interest to combat illegal logging (Lowe and Cross 2011;Lowe et al 2016). Several studies have shown the ability of barcoding to effectively discriminate important timber species, such as agarwood (Aquilaria) (Jiao et al 2014;Lee et al 2016), oak (Quercus) (Deguilloux and Petit 2004), and mahogany (Swietenia) (Degen et al 2013). More recent studies have included Dalbergia species, focusing on species identification in Southeast Asia and Madagascar (Hartvig et al 2015;Hassold et al 2016;Yu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The successfulness of amplification using trnL-trnF have been reported in previous research for Aquilaria, Styrax sumatrana, Shorea, Taxus sumatrana, and Dipterocarpus [33][34][35][36][37]. Furthermore, Fig.…”
Section: Pcr Amplificationsupporting
confidence: 55%
“…Agarwood is widely used as traditional drug, interior decoration and valuable perfume for thousands of years in Asia (Hashim et al 2016). The genus Aquilaria is well known as the main material of the agarwood (Lee et al 2016). Unfortunately, due to the overharvesting of wild resources for high demand of agarwood products, all Aquilaria species are currently endangered and regulated under the CITES (http://checklist.cites.org).…”
mentioning
confidence: 99%